Investigating the role of path architecture complexity in users’ movement patterns in hospital circulation systems: case studies in Golestan, Iran - Saeidi, Maryam; Siyahkali, Mahsa Delshad; Moradinasab, Hossein; Naseri, Gholamhossein (Facilities (Bradford, West Yorkshire, England), 2024)
Purpose This study aims to explore how users’ movement is influenced by different hospital ward layouts, by using space syntax theory. This study also compared four circulation patterns to find the best one for the study goal. Design/methodology/approach The authors used both qualitative and quantitative methods to study how users’ wayfinding in hospitals depends on various indicators and factors. The study used Depth Map software to do case studies and then analyzed the indicators from theoretical foundations and used the Pearson Test to check the correlation between indicators. This study also looked at Iran’s Ministry of Health standards for ward layouts. Finally, the results obtained from the research data were compared to achieve a suitable model based on the research objectives. Findings The linear-patterned plan was the best for easy wayfinding and accessibility among four patterns. The optimal hospital circulation patterns can improve wayfinding and reduce wayfinding problems and user movement. Originality/value By pioneering space syntax in hospital research, this study unveils the novel interaction between path architecture and user movement. It gives new insights into current trends, helping architects, administrators and policymakers improve health-care design, efficiency and patient experience.